Controversies and management of lumbar spine injuries in tennis - Hainline, B. (2000)
Lumbar spine injuries are common in elite tennis players. The majority of such injuries are either acute or recurrent muscle strains. In this lecture, two players will be presented. Both players presented during a high level tennis tournament, one representing an acute disc herniation, and one representing lumbar facet syndrome. Management controversies will be discussed with each case.